Colorful marble tile and manufacturing method thereof

Through local fixed-point application of fantasy dry-grain glaze and combined with full polishing technology of protective glaze layer, the problem that traditional marble tiles are difficult to express fantasy effects is solved, and a more realistic fantasy effect and high-performance marble tiles are achieved.

CN119118710APending Publication Date: 2024-12-13QINGYUAN GANI CERAMICS CO LTD +2
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411257313.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional marble tiles are difficult to effectively express the magic effect of natural marble. The existing magic color dry-grain glaze layer affects the texture clarity of the brick surface when adding scintillation dry particles.

Method used

Local fixed-point application of magic colored dry particles to increase the proportion of flickering dry materials, and wrap high-melting dry particles with transparent dry particles with low melting point to form a light refractive layer, combined with the protective glaze layer to fully polish to maintain flatness and anti-fouling performance .

Benefits of technology

It achieves a more realistic color effect and three-dimensional flickering effect, improving the ornamentality and performance of marble tiles, ensuring that the brick surface is flat and does not affect the anti-fouling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118710A_ABST
    Figure CN119118710A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of architectural ceramics, and particularly relates to a fantasy-color marble tile and a manufacturing method thereof.The manufacturing method comprises the steps that ground coat is applied to the surface of a ceramic tile blank, and then marble texture patterns are printed in an ink-jet mode; carrying out silk-screen printing on colored glaze; applying fantasy-color dry granular glaze on the surface of the colored glaze in a local positioning manner; spraying protective glaze; firing and molding; and polishing and waxing. According to the scheme, the components of the colorful dry granular glaze are improved, and the colorful dry granular glaze is locally applied, so that the fired marble tile can form a vivid colorful effect, and the overall texture definition of the tile surface is not influenced. And moreover, a layer of protective glaze is sprayed on the surface, so that the flickering dry particles are distributed on the upper and lower parts of the glaze layer, a three-dimensional flickering colorful effect is formed, and the three-dimensional flickering colorful effect on the surface cannot be influenced even if the glaze layer is polished.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building ceramics, and in particular to a colorful marble tile and a manufacturing method thereof. Background Art

[0002] Traditional marble tile manufacturing focuses on texture and inkjet color matching. It is difficult to effectively express the color changes caused by the refraction of light in the stone crystals in natural marble. However, the color effect produced by the decomposition of light by these stone crystals is the most fascinating part of the stone.

[0003] Currently, when making the iridescent dry particle glaze layer in the industry, transparent dry particles are usually used as the base material, in which a small amount of glittering dry particles (1-3%) are mixed and applied to the entire surface to achieve the effect of sporadic glittering on the brick surface. It cannot truly and completely replicate the iridescent effect of natural marble, but if the amount of glittering dry particles added is too large, it will affect the clarity of the brick surface texture. Summary of the invention

[0004] In view of the above problems, the present invention provides a colorful marble and a method for manufacturing the same by improving the composition and process of the existing colorful dry particle glaze layer.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for manufacturing colorful marble comprises the following steps:

[0007] (1) Applying a base glaze on the surface of the ceramic tile blank and then inkjet printing a marble texture pattern;

[0008] (2) applying colored glaze by screen printing on the surface of the ceramic tile obtained in step (1);

[0009] (3) applying a colorful dry granule glaze locally on the surface of the colored glaze, wherein the colorful dry granule glaze is mixed with 40-50 parts of transparent dry granules, 20-30 parts of scintillating dry granules, 20-30 parts of printing ink, and 10-15 parts of printing paste; in terms of weight percentage, the chemical composition of the transparent dry granules is SiO2 55-60%, Al2O3 5.5-8.5%, Fe2O3 0-0.3%, CaO 10-15%, MgO 0.2-0.3%, BaO 1.5-4%, ZnO 8-15%, K2O 5-9%, Na2O 0-3%, ZrO2 0.2-0.5%, TiO2 0-1.5%, and the rest is ignition loss; the chemical composition of the scintillating dry granules is SiO2 30-40%, ZrO2 60-70%, Al2O3 0-1%, CaO0-1%, TiO2 0-1%, and the rest is loss on ignition;

[0010] (4) applying protective glaze on the surface of the ceramic tile obtained in step (3);

[0011] (5) firing the bricks obtained in step (4) into shape;

[0012] (6) Polishing and waxing the bricks obtained in step (5).

[0013] The scheme of the present invention can increase the proportion of shimmering dry materials in the shimmering dry granular glaze by adopting local fixed-point application of the shimmering dry granular glaze. Moreover, in the shimmering dry granular glaze, since the transparent dry granules used in the present invention have a low melting point, during the firing process, the shimmering dry granules with a high melting point are first melted and wrapped, so that the wrapped shimmering dry granules in the glaze layer can be stacked layer by layer to form a light refraction layer, thereby forming a more realistic shimmering effect. Further combined with the protective glaze layer, since the protective glaze has a certain thickness in the glaze layer, it can be fully polished to make the brick surface smooth without damaging the underglaze layer. It can provide a higher cutting amount for the polishing of the brick surface without affecting the anti-fouling and other properties of the brick surface. Moreover, since a layer of protective glaze is poured on the surface, the shimmering dry particles are distributed above and below the glaze layer, forming a three-dimensional shimmering shimmering effect, and even polishing will not affect the three-dimensional effect of the shimmering shimmering on the surface. Moreover, after polishing and waxing, the brick surface is smoothed. Due to the high gloss, good flatness and transparent glaze of the brick surface, the light can well illuminate the shimmering dry particles in the glaze and be refracted by a large number of shimmering dry particles, producing a realistic fantasy color gradient effect.

[0014] Preferably, in step (2), the screen is adjusted so that the colors of different textures of the screen are intertwined, so that the transition of the tiles is natural, which can make up for the shortcomings of inkjet printing in color richness, brightness and layering, and enhance the ornamental value of the marble tiles.

[0015] Preferably, in step (3), in the colorful dry particle glaze, the ratio of colorful dry particles to scintillating dry particles is 1:0.4-0.6 by mass, and the finally obtained ceramic tile has good colorful effect and modulus of rupture.

[0016] Preferably, in step (3), the amount of the colorful dry granular glaze applied is 1-1.2 kg / m 2 , thickness 0.75-1.5mm.

[0017] Preferably, in step (3), the particle size of the transparent dry particles is 37-75 μm, and the particle size of the scintillation dry particles is 150-250 μm.

[0018] Preferably, in step (4), the protective glaze is a slurry formed by dispersing protective glaze powder in water, wherein the chemical composition of the protective glaze powder is SiO2 40-45%, Al2O3 6-10%, Fe2O3≤0.3%, CaO 6-10%, MgO 3-6%, BaO 7-12%, ZnO 3-6%, K2O 2-5%, Na2O 2-5%, SrO 2-5%, SO3 1-2.5%, TiO2≤0.5%, and the rest is loss on ignition.

[0019] Preferably, in step (4), the amount of protective glaze applied is 400-600 g / m 2 , in order to reach a certain thickness, which is conducive to polishing and waxing to form a smooth and bright surface.

[0020] Preferably, in step (5), the firing temperature is 1185-1225° C. and the firing time is 45-60 min. If the temperature is too low or the time is too short, the glaze of the tile will not be completely melted and vitrified, thus affecting the transparency of the tile surface.

[0021] Preferably, in step (6), the brightness of the base brick surface after polishing is between 70°-80°, and the brightness of the base brick surface after waxing is between 90°-100°, so that the brick surface is smooth and transparent, and under the irradiation of light, the magic color effect is better presented locally.

[0022] Preferably, in step (6), the polishing process is to first use 10 groups of 400-mesh elastic grinding blocks, 10 groups of 600-mesh elastic grinding blocks, and a pressure of 4kg; then 10 groups of 800-mesh elastic grinding blocks, 10 groups of 1000-mesh elastic modules, and a pressure of 2kg; and finally 20 groups of 240-mesh sponge polishing, and a pressure of 0.5kg. The waxing process can choose commonly used ceramic polishing wax. For example, in a specific embodiment of the present invention, Shuangyi Zhongguang wax is used, and the dripping amount is 12-15g / m 2

[0023] Another aspect of the present invention also provides a colorful marble tile prepared by the above manufacturing method.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The scheme of the present invention improves the components of the colorful dry granule glaze and applies the colorful dry granule glaze locally, so that the fired marble tiles can form a realistic colorful effect without affecting the overall texture clarity of the tile surface. In addition, since a layer of transparent protective glaze of a certain thickness is poured on the surface, the flashing dry particles are distributed above and below the glaze layer, forming a three-dimensional flashing colorful effect. Even polishing will not affect the three-dimensional effect of the flashing colorful surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of the firing effect of tiles in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described by the following embodiments, and it should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention. In the absence of special instructions, the parts are all parts by weight.

[0028] The following is an exemplary description of the method for manufacturing the colorful marble tile of the present invention.

[0029] A method for manufacturing colorful marble comprises the following steps:

[0030] (1) Applying a base glaze on the surface of the ceramic tile blank and then inkjet printing a marble texture pattern;

[0031] The green body can be obtained by forming ordinary ceramic base materials through a press.

[0032] Then, the green body can be dried for 1 to 1.5 hours, and the moisture content of the dried green body can be controlled at 0.3 to 0.5%.

[0033] Then, a base glaze is applied on the blank. The base glaze material is not particularly limited, and the base glaze material known in the art can be used.

[0034] There is no special requirement for the method of applying the base glaze, and the conventional method of preparing the glaze slurry in the art can be used, such as spraying the glaze with an inkjet printer.

[0035] Printing marble texture patterns on the base glaze layer can be done with a digital inkjet printer. The ceramic inks used can be blue, brown, orange, lemon yellow, black, red, etc.

[0036] (2) Applying colored glaze by screen printing on the surface of the ceramic tile obtained in step (1).

[0037] Color glaze is applied on the surface of the blank after inkjet printing by screen printing, and different color glazes are selected according to needs. The screen printing method can be a conventional method in the art. By applying the color glaze, the color can be further enriched.

[0038] (3) Apply colorful dry granular glaze locally on the surface of the colored glaze.

[0039] Usually, the iridescent glaze is applied all over the surface, but the solution of the present invention adopts partial application to highlight the iridescent effect and avoid the problem of flickering and lack of iridescent effect caused by small amount of iridescent dry material when applying all over the surface.

[0040] The colorful dry granule glaze used in the scheme of the present invention is mixed with 40-50 parts of transparent dry granules, 20-30 parts of scintillating dry granules, 20-30 parts of printing oil, and 10-15 parts of printing paste. The chemical composition of the transparent dry granules is SiO2 55-60%, Al2O3 5.5-8.5%, Fe2O3 0-0.3%, CaO 10-15%, MgO 0.2-0.3%, BaO 1.5-4%, ZnO 8-15%, K2O 5-9%, Na2O0-3%, ZrO2 0.2-0.5%, TiO2 0-1.5%; the chemical composition of the scintillating dry granules is SiO2 30-40%, ZrO2 60-70%, Al2O3 0-1%, CaO 0-1%, TiO2 0-1%.

[0041] Preferably, in the colorful dry particle glaze, the ratio of transparent dry particles to scintillating dry particles is 1:0.4-0.6 (mass ratio). In this way, not only the finally obtained ceramic tile has a good colorful effect, but also the product has a good modulus of rupture and strong impact resistance.

[0042] The printing ink and printing paste are the printing ink and printing paste raw materials commonly used in the ceramic field. Preferably, the viscosity of the printing ink is 1000-1200 mpa·s, and the viscosity of the printing paste is 7000-7500 mpa·s.

[0043] Preferably, the amount of the colorful dry granular glaze applied is 1-1.2 kg / m 2 , thickness 0.75-1.5mm.

[0044] Preferably, the particle size of the transparent dry particles is 37-75 μm, and the particle size of the scintillation dry particles is 150-250 μm.

[0045] By adopting local fixed-point application of the fantasy color dry particle glaze, the proportion of shimmering dry materials in the fantasy color dry particle glaze can be increased. Moreover, in the fantasy color dry particle glaze of the present invention, by optimizing the composition of transparent dry materials and shimmering dry particles, the transparent dry particles have a lower melting point. During the firing process, the shimmering dry particles with a high melting point are melted first, so that the shimmering dry particles wrapped in the glaze layer can be stacked layer by layer to form a light refraction layer, thereby forming a more realistic fantasy color effect.

[0046] (4) applying protective glaze on the surface of the ceramic tile obtained in step (3).

[0047] By pouring protective glaze, the glaze layer has a certain thickness after firing, and it can be fully polished to make the brick surface flat without damaging the iridescent layer under the glaze. It can provide a higher cutting amount for brick surface polishing without affecting the anti-fouling properties of the brick surface. Moreover, after polishing and waxing, the brick surface is smoothed. Due to the high gloss, good flatness and transparent glaze surface of the brick surface, the light can well illuminate the glittering dry particles in the glaze surface, and refracted by a large number of glittering dry particles, producing a realistic iridescent gradient effect.

[0048] Protective glaze is a slurry formed by dispersing protective glaze powder in water to facilitate pouring glaze. Commonly used dispersants include sodium tripolyphosphate, sodium methyl cellulose, etc. Protective glaze is usually obtained by mixing protective glaze powder, water and dispersant by ball milling.

[0049] The chemical composition of the protective glaze powder of the protective glaze of the present invention is SiO2 40-45%, Al2O3 6-10%, Fe2O3≤0.3%, CaO 6-10%, MgO 3-6%, BaO 7-12%, ZnO 3-6%, K2O 2-5%, Na2O 2-5%, SrO 2-5%, SO3 1-2.5%, TiO2≤0.5%, and the rest is loss on ignition.

[0050] Preferably, the amount of protective glaze applied is 400-600g / m 2 , in order to reach a certain thickness, which is conducive to polishing and waxing to form a smooth and bright surface.

[0051] In a specific embodiment of the present invention, the protective glaze is prepared by ball-milling 66.3 parts of protective glaze powder, 33.2 parts of clean water, 0.3 parts of sodium tripolyphosphate, and 0.2 parts of sodium methyl cellulose.

[0052] (5) firing the bricks obtained in step (4) into shape;

[0053] The green body is put into the kiln for firing. The firing temperature is 1185-1225℃ and the firing time is 45-60min. If the temperature is too low or the firing time is too short, it is easy to cause the glaze of the tile to not be completely melted and vitrified, affecting the transparency of the tile surface.

[0054] (6) Polishing and waxing the bricks obtained in step (5).

[0055] After firing, it can be polished and waxed. For example, the surface of the tile can be polished with a high-speed rotating diamond brush to make it present a marble-like texture and a magical effect. It can be fully polished to make the surface have a higher gloss and flatness. Full polishing means that the entire surface is polished, and the polishing thickness is thicker, for example, 0.1-0.4mm, to polish the surface into a mirror effect. Through full polishing, a part can be polished off, with a certain glossiness, such as 25-35 degrees. It can also be half-polished. Half-polishing means that the surface is polished to increase the glossiness.

[0056] Preferably, the brightness of the base brick surface after polishing is between 70-80°, and the brightness of the base brick surface after waxing is between 90°-100°, so that the brick surface is smooth and transparent, and under the irradiation of light, the fantasy color effect is better presented locally.

[0057] Preferably, the polishing process is to first use 10 groups of 400 mesh elastic grinding blocks, 10 groups of 600 mesh elastic grinding blocks, and a pressure of 4kg; then 10 groups of 800 mesh elastic grinding blocks, 10 groups of 1000 mesh elastic modules, and a pressure of 2kg; and finally 20 groups of 240 mesh sponge polishing, and a pressure of 0.5kg. The waxing process can choose commonly used ceramic polishing wax. For example, in a specific embodiment of the present invention, Shuangyi Zhongguang wax is used, and the drop coating amount is 12-15g / m 2 .

[0058] The following is further described in conjunction with specific embodiments.

[0059] Table 1 Formula of colorful dry glaze in various embodiments

[0060] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Transparent dry granules 40 45 50 45 25 Flash dry particles 20 25 30 15 35 Printing ink 20 25 30 20 20 Printing paste 10 12 15 10 10

[0061] Table 2 Chemical composition of transparent dry granules in various embodiments

[0062] Example 1 Example 2 Example 3 SiO2 58.07 55.14 59.98 Al2O3 7.06 5.62 8.34 Fe2O3 0.12 0.21 0.15 CaO 12.38 14.18 10.34 MgO 0.26 0.28 0.21 BaO 2.49 3.46 1.62 ZnO 11.22 13.56 8.76 K2O 7.64 5.03 7.12 Na2O 0.22 0.76 2.47 ZrO2 0.29 0.34 0.23 TiO2 0.05 1.12 0.04 Loss on ignition margin margin margin

[0063] Table 3 Chemical composition of scintillation dry particles in various embodiments

[0064]

[0065]

[0066] Table 4 Chemical composition of protective glaze in various embodiments

[0067] Example 1 Example 2 Example 3 SiO2 44.54 40.12 43.71 Al2O3 9.87 8.03 7.14 Fe2O3 0.17 0.28 0.22 CaO 9.77 8.52 7.04 MgO 4.46 3.71 5.89 BaO 7.07 9.68 11.46 ZnO 4.81 3.42 5.38 K2O 4.68 4.03 3.84 Na2O 3.66 3.81 2.03 SrO3 3.22 2.03 4.66 SO3 1.36 1.86 2.12 TiO2 0.08 0.33 0.33 Loss on ignition margin margin margin

[0068] Example 1

[0069] A method for manufacturing colorful marble comprises the following steps:

[0070] (1) Applying a base glaze on the surface of the ceramic tile blank and then inkjet printing a marble texture pattern;

[0071] (2) Applying colored glaze by screen printing on the surface of the ceramic tile obtained in step (1).

[0072] (3) Apply colorful dry granular glaze locally on the surface of the colored glaze.

[0073] The application amount of the fantasy dry granular glaze is 1.2kg / m 2 , thickness 1.5mm.

[0074] The fantasy dry granule glaze is made of 40 parts of transparent dry granules, 20 parts of scintillating dry granules, 20 parts of printing oil, and 10 parts of printing paste. The chemical compositions of transparent dry granules and scintillating dry granules are shown in Table 2 and Table 3, respectively. The particle size of transparent dry granules is 37-75μm, and the particle size of scintillating dry granules is 150-250μm. The viscosity of printing oil is 1000-1200mpa·S, and the viscosity of printing paste is 7000-7500mpa·S.

[0075] (4) applying protective glaze on the surface of the ceramic tile obtained in step (3).

[0076] The protective glaze is made by ball grinding 66.3 parts of protective glaze powder, 33.2 parts of clean water, 0.3 parts of sodium tripolyphosphate and 0.2 parts of sodium methylcellulose. The application amount is 400-600g / m 2 The chemical composition of the protective glaze powder of the protective glaze is shown in Table 4.

[0077] (6) firing the bricks obtained in step (4) into shape;

[0078] The green body is put into the kiln for firing at a temperature of 1185-1225°C and a firing time of 60 minutes.

[0079] (6) Polishing and waxing the bricks obtained in step (5).

[0080] The polishing process is to first use 10 groups of 400 mesh elastic grinding blocks, 10 groups of 600 mesh elastic grinding blocks, and a pressure of 4kg; then 10 groups of 800 mesh elastic grinding blocks, 10 groups of 1000 mesh elastic modules, and a pressure of 2kg; finally 20 groups of 240 mesh sponge polishing, and a pressure of 0.5kg2. After polishing, the surface brightness of the base brick is 75°, and then Shuangyi medium wax is waxed, and the drop coating amount is 12g / m 2 After waxing, the surface brightness of the base brick is 92°.

[0081] The final prepared colorful marble tile surface effect is as follows Figure 1 As shown, the brick surface is smooth and transparent. Under the light, it partially presents a colorful effect. The modulus of rupture is 47.8 MPa.

[0082] Example 2

[0083] A method for manufacturing colorful marble comprises the following steps:

[0084] (1) Applying a base glaze on the surface of the ceramic tile blank and then inkjet printing a marble texture pattern;

[0085] (2) Applying colored glaze by screen printing on the surface of the ceramic tile obtained in step (1).

[0086] (3) Apply colorful dry granular glaze locally on the surface of the colored glaze.

[0087] The application amount of the fantasy dry granular glaze is 1.2kg / m 2 , thickness 1.5mm.

[0088] The fantasy dry granule glaze is made of 45 parts of transparent dry granules, 25 parts of scintillating dry granules, 25 parts of printing oil, and 12 parts of printing paste. The chemical compositions of transparent dry granules and scintillating dry granules are shown in Table 2 and Table 3, respectively. The particle size of transparent dry granules is 37-75μm, and the particle size of scintillating dry granules is 150-250μm. The viscosity of printing oil is 1000-1200mpa·S, and the viscosity of printing paste is 7000-7500mpa·S.

[0089] (4) applying protective glaze on the surface of the ceramic tile obtained in step (3).

[0090] The protective glaze is made by ball grinding 66.3 parts of protective glaze powder, 33.2 parts of clean water, 0.3 parts of sodium tripolyphosphate and 0.2 parts of sodium methylcellulose. The application amount is 400-600g / m 2 The chemical composition of the protective glaze powder of the protective glaze is shown in Table 4.

[0091] (5) firing the bricks obtained in step (4) into shape;

[0092] The green body is put into the kiln for firing at a temperature of 1185-1225°C and a firing time of 60 minutes.

[0093] (6) Polishing and waxing the bricks obtained in step (5).

[0094] The polishing process is to first use 10 groups of 400 mesh elastic grinding blocks, 10 groups of 600 mesh elastic grinding blocks, and a pressure of 4kg; then 10 groups of 800 mesh elastic grinding blocks, 10 groups of 1000 mesh elastic modules, and a pressure of 2kg; finally 20 groups of 240 mesh sponge polishing, and a pressure of 0.5kg2. After polishing, the surface brightness of the base brick is 75°, and then Shuangyi medium wax is waxed, and the drop coating amount is 12g / m 2 After waxing, the surface brightness of the base brick is 92°.

[0095] The finally prepared iridescent marble tiles have a smooth and transparent surface. Under the irradiation of light, they partially show a iridescent effect, and the modulus of rupture is 46.9 MPa.

[0096] Example 3

[0097] A method for manufacturing colorful marble comprises the following steps:

[0098] (1) Applying a base glaze on the surface of the ceramic tile blank and then inkjet printing a marble texture pattern;

[0099] (2) Applying colored glaze by screen printing on the surface of the ceramic tile obtained in step (1).

[0100] (3) Apply colorful dry granular glaze locally on the surface of the colored glaze.

[0101] The application amount of the fantasy dry granular glaze is 1.2kg / m 2 , thickness 1.5mm.

[0102] The fantasy dry granule glaze is made of 50 parts of transparent dry granules, 30 parts of scintillating dry granules, 30 parts of printing oil, and 15 parts of printing paste. The chemical compositions of transparent dry granules and scintillating dry granules are shown in Table 2 and Table 3, respectively. The particle size of transparent dry granules is 37-75μm, and the particle size of scintillating dry granules is 150-250μm. The viscosity of printing oil is 1000-1200mpa·S, and the viscosity of printing paste is 7000-7500mpa·S.

[0103] (4) applying protective glaze on the surface of the ceramic tile obtained in step (3).

[0104] The protective glaze is made by ball grinding 66.3 parts of protective glaze powder, 33.2 parts of clean water, 0.3 parts of sodium tripolyphosphate and 0.2 parts of sodium methylcellulose. The application amount is 400-600g / m 2 The chemical composition of the protective glaze powder of the protective glaze is shown in Table 4.

[0105] (5) firing the bricks obtained in step (4) into shape;

[0106] The green body is put into the kiln for firing at a temperature of 1185-1225°C and a firing time of 60 minutes.

[0107] (6) Polishing and waxing the bricks obtained in step (5).

[0108] The polishing process is to first use 10 groups of 400 mesh elastic grinding blocks, 10 groups of 600 mesh elastic grinding blocks, and a pressure of 4kg; then 10 groups of 800 mesh elastic grinding blocks, 10 groups of 1000 mesh elastic modules, and a pressure of 2kg; finally 20 groups of 240 mesh sponge polishing, and a pressure of 0.5kg2. After polishing, the surface brightness of the base brick is 75°, and then Shuangyi medium wax is waxed, and the drop coating amount is 12g / m 2 After waxing, the surface brightness of the base brick is 92°.

[0109] The finally prepared iridescent marble tiles have a smooth and transparent surface. Under the irradiation of light, they partially show a iridescent effect, and the modulus of rupture is 46.1 MPa.

[0110] Comparative Example 1

[0111] The difference from Example 1 is that the amount of each component in the magic color dry particle glaze is different, and the mass ratio is transparent dry particles: scintillating dry particles = 3:1, and the rest are the same. The modulus of rupture of the final obtained tile is 46.7 MPa, but due to the small amount of scintillating dry particles accumulated in the glaze layer, the magic color effect is not obvious.

[0112] Comparative Example 2

[0113] The difference from Example 1 is that the amount of each component in the magic color dry granule glaze is different. According to the mass ratio, the transparent dry granules: the scintillating dry granules = 5:7, and the rest are the same. The modulus of rupture of the final tile is 41.6 MPa. Since the amount of scintillating dry granules accumulated in the glaze layer is too large, they cannot be completely wrapped during the firing process, resulting in cracks inside the glaze layer, affecting the surface effect and reducing the performance of the tile surface.

[0114] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0115] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for manufacturing colorful marble tiles, characterized in that: The following steps are involved: (1) Applying a base glaze on the surface of the ceramic tile blank and then inkjet printing a marble texture pattern; (2) applying colored glaze by screen printing on the surface of the ceramic tile obtained in step (1); (3) Applying a colorful dry granule glaze locally on the surface of the colored glaze; the colorful dry granule glaze is mixed by 40-50 parts of transparent dry granules, 20-30 parts of scintillating dry granules, 20-30 parts of printing ink, and 10-15 parts of printing paste in terms of weight percentage; the chemical composition of the transparent dry granules is SiO2 55-60%, Al2O3 5.5-8.5%, Fe2O3 0-0.3%, CaO 10-15%, MgO0.2-0.3%, BaO 1.5-4%, ZnO 8-15%, K2O 5-9%, Na2O 0-3%, ZrO2 0.2-0.5%, TiO20-1.5%, and the rest is ignition loss; the chemical composition of the scintillating dry granules is SiO2 30-40%, ZrO2 60-70%, Al2O3 0-1%, CaO 0-1%, TiO2 0-1%; the rest is loss on ignition; (4) applying protective glaze on the surface of the ceramic tile obtained in step (3); (5) firing the bricks obtained in step (4) into shape; (6) Polishing and waxing the bricks obtained in step (5).

2. The manufacturing method according to claim 1, characterized in that: In the step (2), the screen is adjusted so that the colors of different textures of the screen are mutually infiltrated.

3. The manufacturing method according to claim 1, characterized in that: In the step (3), according to the mass ratio, in the colorful dry particle glaze, the transparent dry particles: the shimmering dry particles = 1: 0.4-0.

6.

4. The manufacturing method according to claim 1, characterized in that: In the step (3), the amount of the colorful dry granular glaze applied is 1-1.2 kg / m 2 , thickness 0.75-1.5mm.

5. The manufacturing method according to claim 1, characterized in that: In the step (3), the particle size of the transparent dry particles is 37-75 μm, and the particle size of the scintillation dry particles is 150-250 μm.

6. The manufacturing method according to claim 1, characterized in that: In the step (4), the protective glaze is a slurry formed by dispersing protective glaze powder in water; in terms of weight percentage, the chemical composition of the protective glaze powder is SiO2 40-45%, Al2O3 6-10%, Fe2O3 ≤ 0.3%, CaO 6-10%, MgO 3-6%, BaO 7-12%, ZnO 3-6%, K2O 2-5%, Na2O 2-5%, SrO 2-5%, SO3 1-2.5%, TiO2 ≤ 0.5%, and the rest is loss on ignition.

7. The manufacturing method according to claim 1, characterized in that: In the step (4), the amount of protective glaze applied is 400-600g / m 2 .

8. The manufacturing method according to claim 1, characterized in that: In the step (5), the firing temperature is 1185-1225° C., and the firing time is 45-60 min.

9. The manufacturing method according to claim 1, characterized in that: In the step (6), the surface brightness of the base brick after polishing is between 70° and 80°, and the surface brightness of the base brick after waxing is between 90° and 100°.

10. A colorful marble tile, characterized in that: The method is prepared by the manufacturing method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Mica sheet decorative ceramic glazed tile and preparation method thereof

    CN110451802A

  • Ceramic tile with three-dimensional gem granular glaze surface and preparation method of ceramic tile

    CN112500196A

  • Glittery cover glaze and preparation method thereof, and preparation method of ceramic tile with glittery effect

    CN112707642A

  • Treatment method capable of realizing glimmering surface of fine dry-grained rock plate

    CN114057397A

  • Flash dry granular glaze, flash dry granular polished ceramic plate and preparation method of flash dry granular glaze and flash dry granular polished ceramic plate

    CN114213013A